Single Session Thinking 2020. Issue 3 (7th October 2020) - Hoyt, Michael F.; Young, Jeff; Rycroft, Pam
Abstract : This update presents key developments since Talmon's original (1990) publication, including an account of the three international symposia which have taken place since the last ANZJFT special edition on single session therapy in 2012, and the major compilations that followed the symposia. Underlying elements that unite different single session approaches are explored, and an attempt is made to provide a terminology that is inclusive and coherent. As reflected in the title, the term 'single session thinking' is suggested as an over‐arching term for the approach that is no longer limited to the therapy room, but reaches into many different contexts. In conclusion, possible future clinical and research developments in the field of single session thinking and practice are reflected upon, and the implications for contemporary health care delivery considered.